Sosialisasi Peningkatan Soft Skills Melalui Pembentukan Karakter Terintegral pada Anak Yatim Piatu - Islami, Mega; Waluyo, Minto (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
Children are national assets that have the right to be protected, a child must receive protection and education. The current development of digital technology provides changes in behavior for children and society in carrying out activities. The problem faced by children at the Yakarim orphanage is a lack of knowledge and soft skills, this is due to the lack of education and training provided so that they cannot form an integrated character. This socialization aims to shape the character of orphanage children with better quality to face industrial competition. The method used is descriptive qualitative to train children's thinking skills, develop their potential, provide motivation to think innovatively, and produce work by utilizing existing resources. Keywords: Soft skills, Integral Character, Orphan